Giant Fibroadenoma in a Middle-Aged Woman Requiring Mastectomy: A Case Report - Nwashilli NJ; Obahiagbon I (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2020)
Fibroadenomas are benign tumours of the breast. They are usually single, firm, rubbery masses, slow-growing and well encapsulated. Giant fibroadenomas are fibroadenomas at least 5cm in size or at least 500g in weight. The peculiarities of the index case include the massive size and weight of the breast, causing asymmetry and tissue distortion with little or no normal breast tissue on ultrasound scan. Also, such massive weight has not been reported in the literature as suggested by extensive search on databases such as Pubmed and Google Scholar. The main concern of the patient was the rapid growth over a year, with the attendant risk of malignancy. The mass was firm, lobulated, with a solitary axillary lymph node. An initial clinical diagnosis of phyllodes tumour was made. However, pre-operative Tru-cut biopsy histology suggested fibroadenoma and was confirmed using the excised post-operative specimen. Simple mastectomy with axillary lymph node excision was carried out. In conclusion, a large breast tumour may not be malignant. However, mastectomy may be a treatment option despite the benign nature of the tumour.